2018
DOI: 10.1111/jocn.14285
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of change in cognitive function in people with chronic obstructive pulmonary disease

Abstract: Understanding the trajectories of change in cognitive function and predictors of change in cognitive function over 3 years may enable health care providers to identify patients at greatest risk of developing mental deterioration and those who might benefit from interventions to improve cognitive function. Health care providers should periodically assess and frequently screen people with COPD for cognitive function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…They influence the rate of differentiation and apoptosis of cerebral cells [137] and regulate long-term potentiation [138] and hippocampal neurogenesis [137]. Multiple previous studies have shown the benefit of exercise on cognition in COPD patients [139,140], and in the study by Park et al the 6-minute walking distance was the only potentially modifiable variable that was related to worsening cognitive functioning over time [27]. The question remains, however, whether these improvements consolidate into the longer term if exercise is discontinued [11].…”
Section: Exercise Trainingmentioning
confidence: 98%
See 1 more Smart Citation
“…They influence the rate of differentiation and apoptosis of cerebral cells [137] and regulate long-term potentiation [138] and hippocampal neurogenesis [137]. Multiple previous studies have shown the benefit of exercise on cognition in COPD patients [139,140], and in the study by Park et al the 6-minute walking distance was the only potentially modifiable variable that was related to worsening cognitive functioning over time [27]. The question remains, however, whether these improvements consolidate into the longer term if exercise is discontinued [11].…”
Section: Exercise Trainingmentioning
confidence: 98%
“…This surprising result might be explained by survival bias rather than the effects of COPD itself [26]. In a recent study, 32.6% of patients taking part in the National Emphysema Treatment Trial (NETT) were impaired on part B of the Trail Making Test (TMT) at baseline [27]. This test measures task switching, which is part of executive functioning.…”
Section: Longitudinal Studiesmentioning
confidence: 99%
“…Cognitive impairment in elderly patients with COPD is affected by various factors, including disease-specific factors such as hypoxemia, 19 hypercapnia, 20 and systemic inflammation, 21 and lifestyle factors such as diet deficiency, 22 and lack of physical activity; 23,24 Other factors, such as aging, 25 long-term smoking, 26,27 education, 28 severity, and course of the disease, 29 may lead to abnormality in the brain structure and function in COPD patients, resulting in cognitive impairment. Moreover, elderly patients with COPD varying in degrees of synergy are often accompanied by cerebrovascular disease, anxiety and depression, sleep disorders, metabolic syndrome and other complications.…”
Section: Influencing Factors Of Cognitive Impairment In Elderly Patiementioning
confidence: 99%
“…However, these results are primarily from relatively healthy populations, with normal levels of cognitive functioning, and perhaps leave little room for improvement. Individuals with COPD more frequently experience cognitive impairment (10); approximately 56.7% of patients with COPD are affected by cognitive impairment, compared to 13.3% of aged matched peers (10), which can also worsen over time (25,26). When cognitive function is affected, typically attention, memory, executive functions and WM are affected (27,28).…”
Section: Why Consider Cognitive Training In the Overall Management Ofmentioning
confidence: 99%